2022
DOI: 10.1093/eurpub/ckac085
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mass-media campaigns on physical activity: a review of reviews through a policy lens

Abstract: Background This review of reviews aimed to: (1) summarize the evidence from published reviews on the effectiveness of mass-media campaigns to promote physical activity (PA) or PA-related determinants (intermediate psychological and proximal outcomes) and (2) to identify policy-relevant recommendations related to successful PA campaigns. Methods An extensive literature search was performed on 1 March 2021. Reviews that evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Our findings of the poor methodological quality of SRs in the food field are in line with those from assessments of the methodological quality of SRs that used the AMSTAR 2 tool in other fields, including acupuncture [16,17], dentistry [18], Tai Chi [19,20], surgery [21,22], major depression in adults [23], chronic obstructive pulmonary disease [24], cardiovascular risk [25], physical activity [26], pancreatic cancer [27], chronic heart failure [28], cancerrelated fatigue [29], Alzheimer's disease [30], chronic spinal pain [31], neonatal pain [32], hip fractures [33], and atopic eczema [34]. Although the target patients or participants and interventions in those studies differed between each study, all demonstrated that the majority of SRs included had low methodological quality ("low" or "critically low").…”
Section: Findings In Contextsupporting
confidence: 83%
“…Our findings of the poor methodological quality of SRs in the food field are in line with those from assessments of the methodological quality of SRs that used the AMSTAR 2 tool in other fields, including acupuncture [16,17], dentistry [18], Tai Chi [19,20], surgery [21,22], major depression in adults [23], chronic obstructive pulmonary disease [24], cardiovascular risk [25], physical activity [26], pancreatic cancer [27], chronic heart failure [28], cancerrelated fatigue [29], Alzheimer's disease [30], chronic spinal pain [31], neonatal pain [32], hip fractures [33], and atopic eczema [34]. Although the target patients or participants and interventions in those studies differed between each study, all demonstrated that the majority of SRs included had low methodological quality ("low" or "critically low").…”
Section: Findings In Contextsupporting
confidence: 83%
“…The third category includes community-level mass media and public education campaigns, which appear to improve PA awareness but have mixed effects on increasing actual PA levels. [41] Lastly, at the individual level, the WHO advocates primary care professional-delivered or prompted PA interventions, which are associated with increased rates of moderate to vigorous PA. [42] Obesity Screening for overweight and obesity in the primary care setting is an important individual-level prevention strategy. If detected, the first step is weight loss counseling for diet and PA behavioral change: ranging from brief clinic encounters to intensive multicomponent behavioral interventions.…”
Section: Physical Activitymentioning
confidence: 99%
“…Often based at the workplace or schools, these have demonstrated benefits on PA levels. The third category includes community-level mass media and public education campaigns, which appear to improve PA awareness but have mixed effects on increasing actual PA levels 41 . Lastly, at the individual level, the WHO advocates primary care professional-delivered or prompted PA interventions, which are associated with increased rates of moderate to vigorous PA 42 …”
Section: Interventions For Behavioral Metabolic Risk Factorsmentioning
confidence: 99%
“… 24 and where gaps were found, we undertook new reviews of empirical studies 25–28 and an umbrella review. 29 PEN researchers mapped, reviewed and synthesized all policy actions and recommendations from these three methodologies during an extensive inductive and deductive process. This led to the development of the PA-EPI framework.…”
Section: Development Of a Pa-epi Framework For Monitoring Government ...mentioning
confidence: 99%